Training and Implementation of Smart Career Application for Students for Career Planning in Vocational High Schools - Teguh Setiadi; Laksamana Rajendra Haidar Azani Fajri; Susanti Dwi Ilhami (Universitas Veteran Bangun Nusantara, 2025)
Vocational high school education is an important path to foster skilled professionals with skills in accordance with their fields and is increasingly attracting attention in the world of work. Vocational education emphasizes the development of practical skills and vocational competencies of students. This equips them with the ability to adapt quickly to market demands and contribute to social and economic development, one of which is at SMK Harapan Mulya Kendal. Along with the advancement of globalization and technology, career planning has evolved beyond just career selection; career planning has become a comprehensive process that requires consideration of various factors such as personal interests, values, skills, and job market requirements. The purpose of community service is to provide training for the implementation of smart career applications for vocational high school students, to help them better overcome challenges in the workplace and realize their respective career goals before graduating from school. In the implementation of community service activities with the Implementation and Implementation Method, Training, Mentoring, Monitoring and Evaluation with an emphasis on solving problems, namely student human resources and counseling guidance in order to improve the quality of student careers, and understanding of the career potential of vocational high school students. The conclusion of the training results for guidance and counseling teachers can provide stimulus to each student, in this case the teacher as a supervisor, to increase students' self-confidence in building personality and exploring the potential of each student so that students realize what potential they have in themselves to be confident in their future careers. Keywords: Smart Career Application, Student Career, Student Personality, Vocational High School Career Planning